2017
DOI: 10.1105/tpc.16.00573
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of the Histone Variant H2A.Z in Transcriptional Regulation of Stress-Response Genes

Abstract: The influence of the histone variant H2A.Z on transcription remains a long-standing conundrum. Here, by analyzing the actinrelated protein6 mutant, which is impaired in H2A.Z deposition, and by H2A.Z profiling in stress conditions, we investigated the impact of this histone variant on gene expression in Arabidopsis thaliana. We demonstrate that the arp6 mutant exhibits anomalies in response to osmotic stress. Indeed, stress-responsive genes are overrepresented among those hyperactive in arp6. In wild-type plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
153
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(175 citation statements)
references
References 83 publications
(119 reference statements)
20
153
1
1
Order By: Relevance
“…1b,d). Similarly, the pie1 mutants exhibited more severe developmental and stress response phenotypes than those of the arp6 and hta9 hta11 mutants (Rosa et al, 2013;Sura et al, 2017), which corresponds to the suggested role of PIE1 as a catalytic subunit of the SWR1 complex (Mizuguchi et al, 2004).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…1b,d). Similarly, the pie1 mutants exhibited more severe developmental and stress response phenotypes than those of the arp6 and hta9 hta11 mutants (Rosa et al, 2013;Sura et al, 2017), which corresponds to the suggested role of PIE1 as a catalytic subunit of the SWR1 complex (Mizuguchi et al, 2004).…”
Section: Resultsmentioning
confidence: 58%
“…Mutants deficient in H2A.Z deposition show overaccumulation of anthocyanin Genome-wide analysis showed that the expression of a set of anthocyanin biosynthetic genes was significantly enhanced in the H2A.Z variant deposition-deficient mutant, arp6 (Dai et al, 2017;Sura et al, 2017), suggesting a negative regulatory role of the chromatin remodeling complex, SWR1, and H2A.Z in anthocyanin biogenesis. The SWR1 complex is a member of the INO80 family of chromatin remodelers composed of proteins including PHOTOPERIOD INDEPENDENT EARLY FLOW-ERING1 (PIE1), ACTIN-RELATED PROTEIN (ARP6) and SERRATED LEAVES AND EARLY FLOWERING (SEF) in Arabidopsis (Choi et al, 2007;Deal et al, 2007;March-Diaz et al, 2007;Qin et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In Arabidopsis, three genes encode the pool of H2A.Z proteins and there are no completely null triple H2A.Z mutants available, which complicates genetic work with H2A.Z (Coleman‐Derr and Zilberman, ). arp6 mutants provide a logical proxy for H2A.Z mutants in our genetic study, as other studies have verified that ARP6 is required for proper H2A.Z incorporation into nucleosomes and arp6 mutants phenocopy H2A.Z mutants (March‐Diaz et al ., ; Berriri et al ., ; Sura et al ., ). Therefore, we identified genes that are differentially expressed (DE) in brm‐1 mutants, arp6‐1 mutants and/or arp6‐1;brm‐1 double mutants compared with wild type (WT) plants.…”
Section: Resultsmentioning
confidence: 97%
“…We identified 2109 genes that were DE in arp6 (1036 genes upregulated and 1073 genes downregulated), 4250 genes DE in brm (2317 genes up and 1933 genes down), and 3203 genes DE in arp6;brm mutants (1517 genes up and 1686 genes down) (Figure S1b, summarized in Table S1). The gene sets we defined as DE in arp6‐1 and brm‐1 overlap significantly with those defined in previous studies (Archacki et al ., ; Sura et al ., ). Gene Ontology terms that were overrepresented among DE genes in each mutant were largely associated with responses to biotic and abiotic stress (Table S2).…”
Section: Resultsmentioning
confidence: 97%
“…Several reports in Drosophila (Rhee and Pugh ; Weber et al ) and in Arabidopsis (Sura et al ) suggest that H2A.Z at the +1 nucleosome correlates with transcription activation, whereas a recent study proposed that H2A.Z in gene body associates with transcription repression in Arabidopsis (Sura et al ). For the OsINO80 target genes CPS1 and GA3ox2 , H2A.Z enrichments decrease both close to the +1 nucleosome and within the 3’ gene body in the OsINO80 ‐knockdown mutants, thus the downregulation of these two genes is probably due to synergistic effects.…”
Section: Discussionmentioning
confidence: 99%